The Roles of Insulin-Like Growth Factor 2 mRNA-Binding Protein 2 in Cancer and Cancer Stem Cells - Junguo Cao; Qingchun Mu; Haiyan Huang (Stem Cells International)
RNA-binding proteins (RBPs) mediate the localization, stability, and translation of the target transcripts and fine-tune the physiological functions of the proteins encoded. The insulin-like growth factor (IGF) 2 mRNA-binding protein (IGF2BP, IMP) family comprises three RBPs, IGF2BP1, IGF2BP2, and IGF2BP3, capable of associating with IGF2 and other transcripts and mediating their processing. IGF2BP2 represents the least understood member of this family of RBPs; however, it has been reported to participate in a wide range of physiological processes, such as embryonic development, neuronal differentiation, and metabolism. Its dysregulation is associated with insulin resistance, diabetes, and carcinogenesis and may potentially be a powerful biomarker and candidate target for relevant diseases. This review summarizes the structural features, regulation, and functions of IGF2BP2 and their association with cancer and cancer stem cells.